PENGARUH AUDITOR CLIENT TENURE, UKURAN PERUSAHAAN, PERTUMBUHAN PERUSAHAAN DAN REPUTASI AUDITOR TERHADAP OPINI AUDIT GOING CONCERN (Studi Empiris pada Perusahaan Manufaktur yang terdaftar diBursa Efek Indonesia tahun 2015-2017) - Maya Widyana Dewi; Indra Lila Kusuma (Jurnal Manajemen Terapan dan Keuangan, 2018)
This study aims  to provide empirical  evidence of  the  effect: the client auditor tenure,firmsize,growth,auditor reputation,leverage,and financial distress to thegoing concern audit opinion on manufacturingcompanieslisted in Indonesia Stock Exchange 2015-2017.This research was conducted using secondarydata. Thesample in this study were 28 companies listed on theIndonesian Stock Exchange (BEI) during the period2015-2017. The analytical method use dislogistic regression analysis.Theresultsof this study prove that variable client auditortenure, company size,auditor reputation,and leverage significant influence on the going concern audit opinion,while thecompany's growth variable and financial distress hasno significant effect on the going concern audit opinion on the manufacturing companies in the Indonesia Stock Exchange.